Islamic Educational Institution Al Jam'iyatul Washliyah under the Leadership of Muhammad Arsyad Talib Lubis (1930-1972) - Muhammad Saukani Dabutar; Sarkadi Sakardi; M. Fakhruddin (Improvement: Jurnal Ilmiah untuk Peningkatan Mutu Manajemen Pendidikan, 2024)
This study explores the role of Muhammad Arsyad Thalib Lubis in Islamic education and the organization of Al Jam'iyatul Washliyah in North Sumatra between 1930-1972. This study uses historical methods to reconstruct events related to Muhammad Arsyad Talib Lubis and his influence on the development of Islamic education. Data was collected through literature studies and interviews. The results showed that Muhammad Arsyad Talib Lubis, who was born in Stabat, Langkat, in 1908, had played an essential role in establishing Al Washliyah University and developing Al Jam'iyatul Washliyah from a debating club into an influential educational organization. Lubis died on July 6, 1972, but his legacy and principles still live among Al Washliyah's disciples and the wider community.